LEARNING STRATEGIES FOR ISLAMIC CULTURAL HISTORY AT THE STATE MADRASAH ALIYAH MODEL BUKITTINGGI - Ahmad Nizam; Nurfitria Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Islamic Cultural History (ISH) learning plays an important role in shaping students' historical awareness and Islamic attitudes. However, in madrasah learning, it appears that students' interest in this subject is still low, this is because the teaching methods are still ordinary, boring, and less relevant to everyday life. This study aims to describe various ISH learning strategies used by teachers at MAN Model Bukittinggi, based on students' understanding of the subject matter. This study uses a qualitative descriptive approach and data collection through observation, interviews, and documentation. Data analysis is carried out by reducing data, displaying data, and drawing conclusions, and is supported by the use of diverse sources and specific techniques. The study shows that teachers use various teaching methods, such as interactive speaking, storytelling, learning through projects, utilizing digital media, and teaching with an approach that considers context and reflection. These strategies have proven successful in increasing students' active participation, making them more interested in learning, and deepening their understanding of ISH material. In addition, evaluation is not only based on knowledge, but also through various assessment processes and learning outcomes such as discussions, projects, and group presentations. It can be concluded that SKI learning with diverse, collaborative, and context-specific approaches has the potential to create more meaningful, enjoyable, and life-relevant learning experiences for students. This research also provides assistance in creating a more flexible SKI learning model to address the challenges of 21st-century education.